The jungle book - Kipling, Rudyard, 1865-1936.; Detmold, Maurice; Detmold, Edward Julius, 1883-1957; Kipling, John Lockwood, 1837-1911; Drake, W. H. (New York : Children's Classics, 1989)
Presents the adventures of Mowgli, a boy reared by a pack of wolves, and the wild animals of the jungle. Also includes other short stories set in India.
Wilson's Children
6.3
3-6
Keywords: Mowgli (Fictitious character) -- Fiction; Jungles -- India -- Fiction; Animals -- Fiction; Jungles -- Fiction; Animals -- Fiction; India -- Fiction; Short stories; Jungles -- Fiction; Animals -- Fiction; India -- Fiction; Short stories